Ulnar diaphyseal stress injuries: a case series. Issue 6 (June 2022) - Dean, C.; Davis, I.; Hunt, H.
Abstract : AIM: To describe the demographics, clinical context, imaging findings, and management of a case series of ulnar diaphyseal stress injuries (UDSIs) and propose a unifying mechanism for these injuries based on the imaging findings. MATERIALS AND METHODS: Seven patients from University of Florida College of Medicine (seven total injuries; mean age: 19 ± 4.4 years; three females, four males) with available clinic and imaging data and without predisposing comorbidities were included in this retrospective study. The age, gender, laterality of injury with respect to the dominant hand, attributed inciting activity, imaging method, presence and location of stress injury findings, as well as the subsequent management were analysed. RESULTS: All patients were in the second or third decade of life and there was a slight male predominance to the case series (57%). All UDSIs in this series were unilateral. Fifty-seven percent of injuries involved the dominant ulna and all involved the ulnar diaphysis along the proximal–mid junction, mid diaphysis or mid–distal junction. All injuries involved portion of the ulnar origin of the flexor digitorum profundus (FDP). All patients were managed conservatively. CONCLUSION: UDSIs are uncommon and associated with a broad range of occupational or sports-related activities. All cases in this series involved the ulnar origin of the FDP suggesting an important role for the forces exerted by this muscular attachment on the underlying bone with regard to the development of UDSIs. Highlights: UDSIs are rare and tend to affect younger patients. Familiarity with the imaging findings of UDSIs is important for accurate diagnosis. This study represents the largest case series of UDSIs evaluated with MRI. The forces applied to the bone by the FDP may be important in the development of UDSIs.